Assessing Pedophilic Sexual Interest: The Utility of Objective Correlates in Diagnostic Decisions - Raquel Yeomans; Drew A. Kingston (Sexual Offending, 2025)
Pedophilic sexual interest is a risk factor for sexual recidivism and has particular relevance for a significant proportion of individuals who have sexually offended against a child. In this article, we review the predominant ways in which pedophilia is assessed, including both direct and indirect approaches. The limitations of these methods are highlighted and the utility of incorporating more objective indicators into a comprehensive evaluation is examined. Particular emphasis is placed on the inclusion of behavioral correlates into a comprehensive and multimodal assessment approach. Implications for the assessment of individuals convicted of sexual offending and who present with pedophilic sexual interest are discussed.